2009
DOI: 10.1016/j.jpowsour.2009.06.075
|View full text |Cite
|
Sign up to set email alerts
|

High capacity multicomponent hydrogen storage materials: Investigation of the effect of stoichiometry and decomposition conditions on the cycling behaviour of LiBH4–MgH2

Abstract: a b s t r a c tLiBH 4 -MgH 2 is an attractive reversible hydrogen storage system, it combines two high capacity hydrides (18.3 and 7.6 wt.%, respectively) and the concerted dehydrogenation reaction has a smaller enthalpy change than either species on its own. The latter effect leads to a destabilisation of the hydrided products and results in a lowering of the dehydrogenation temperature. In situ neutron diffraction experiments have been undertaken to characterise the mechanism of decomposition of the LiBD 4 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
41
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 13 publications
11
41
1
Order By: Relevance
“…The overall reaction for hydriding and dehydriding of the LiBH 4 þ MgH 2 mixture (in a 2:1 M ratio) has been generally agreed to be [1]. LiBH 4 þ ½MgH 2 ¼ LiH þ ½MgB 2 þ 2H 2 (1) Furthermore, many studies [2e6, 10] have revealed that the dehydrogenation process is actually composed of two elemental steps, i.e., MgH 2 decomposes into Mg and H 2 first, and then the newly formed Mg react with LiBH 4 to produce LiH, MgB 2 and H 2 , as indicated by the following two reactions [5].…”
Section: Introductionmentioning
confidence: 99%
“…The overall reaction for hydriding and dehydriding of the LiBH 4 þ MgH 2 mixture (in a 2:1 M ratio) has been generally agreed to be [1]. LiBH 4 þ ½MgH 2 ¼ LiH þ ½MgB 2 þ 2H 2 (1) Furthermore, many studies [2e6, 10] have revealed that the dehydrogenation process is actually composed of two elemental steps, i.e., MgH 2 decomposes into Mg and H 2 first, and then the newly formed Mg react with LiBH 4 to produce LiH, MgB 2 and H 2 , as indicated by the following two reactions [5].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The relatively stable alkaline and alkaline earth metal borohydrides form in some cases with transition metals new bimetallic phases, which may improve the thermodynamic properties. [5][6][7][8] Metal borohydrides are known to have a rich chemistry and can also form eutectic melting mixtures as observed for the Ca(BH 4 ) 2 -LiBH 4 system or new solids as in the Al(BH 4 ) 3 -LiBH 4 system, i.e., Li 4 Al 3 (BH 4 ) 13 . 9,10 The thermal stability of binary metal hydrides has been inversely related to the metal electronegativity (and consequently to the standard redox potential).…”
Section: Introductionmentioning
confidence: 99%
“…The results reported by Walker et al [22] for a LiBH 4 eMgH 2 system showed that reversible dehydrogenation of LiBD 4 e MgD 2 in a 2:1 M ratio could be possible under low pressures of hydrogen. Weng et al [23] reported improvement in the dehydrogenation performance of LiBH 4 /MgH 2 composite by addition of Pd nanoparticles.…”
Section: Introductionmentioning
confidence: 92%